Psychometric Properties of the Turkish Version of the Breathlessness Catastrophizing Scale in Patients with Chronic Obstructive Pulmonary Disease - Şerife Demirbaş; İlknur Naz; Elvan Felekoğlu; Melissa Köprülüoğlu; Hülya Şahin (Thoracic Research and Practice)
OBJECTIVE: To examine the validity and reliability of the Turkish version of the Breathlessness Catastrophizing Scale (BCS) in patients with chronic obstructive pulmonary disease (COPD). MATERIAL AND METHODS: Seventy patients with COPD (55 male/15 female, mean age: 68.7±7.3 years, FEV1%: 45.4±19.5) were included in this methodological study. Internal consistency was measured using Cronbach’s α, and intra-rater reliability was assessed using the intraclass correlation coefficient (ICC). Correlations between the BCS and Modified Medical Research Council Dyspnea Scale (mMRCS), COPD Assessment Test (CAT), Hospital Anxiety and Depression Scale (HADS), Breathlessness Beliefs Questionnaire (BBQ), and St. the George Respiratory Questionnaire (SGRQ) scores were assessed for convergent validity. Known-group comparisons were performed according to COPD stage and dyspnea severity using the independent sample t-test. RESULTS: Internal consistency was excellent (Cronbach’s α=0.941), and the ICC for reliability was 0.955. The BCS score was correlated with the mMRCS (r=0.745), CAT (r=0.652), HADS anxiety (r=0.556) and depression (r=0.588), the BBQ (r=-0.567), and SGRQ (r=0.550-0.634) scores (P < 0.05). The BCS score was higher in patients with advanced COPD (P = 0.003) and those with severe dyspnea (P < 0.001). CONCLUSION: The Turkish version of the BCS is a valid and reliable tool for evaluating catastrophic dyspnea in patients with COPD.